PEDAGOGICAL OPPORTUNITIES FOR DEVELOPING THE PROFESSIONAL COMPETENCE OF FUTURE SPEECH THERAPISTS BASED ON THE SUBJECT "SPEECH THERAPY RHYTHMICS" (Scientific journal of the Fergana State University, 2025)
This scientific article is devoted to studying the pedagogical opportunities for developing the professional competence of future speech therapists based on the subject "Speech Therapy Rhythmics." The article discusses the importance of the subject of speech therapy rhythmics in the educational process and its role in forming the professional knowledge, skills, and abilities required for future speech therapists.The main goal of the study is to identify pedagogical approaches and methods that contribute to the development of the professional competence of future speech therapists through the integration of speech therapy rhythmics into the educational process. The article examines the theoretical and practical aspects of speech therapy rhythmics and methods and tools that positively influence students' professional development.The study employed pedagogical experiments, theoretical analysis, and empirical observations to explore the role of speech therapy rhythmics in the educational process. The research findings confirm the effectiveness of speech therapy rhythmics in developing the professional competence of future speech therapists. The article also provides recommendations for the practical application of speech therapy rhythmics in developing professional competencies.The article serves as an important scientific source for expanding the potential of speech therapy rhythmics in preparing future speech therapists, improving the quality of education, and enhancing the pedagogical process.